2015
DOI: 10.1039/c5ra21932a
|View full text |Cite
|
Sign up to set email alerts
|

Reactant cum solvent water: generation of transient λ3-hypervalent iodine, its reactivity, mechanism and broad application

Abstract: We have demonstrated a benign strategy for amides, imides and their chiral analogues using water as a source of carbonyl oxygen and medium. DFT-MIR studies and controlled experiments established the mechanism involving PhI(OH)2-bearing intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…ATR‐MIR spectroscopy disclosed the formation of unknown intermediates in the reaction. NMR and labelling ( 2 H and 18 O) experiments supported the DFT‐IR predicted reaction pathway such as cleavage of triple bond, amination and amidation to afford desired amide [75] …”
Section: Coupling Reactionsmentioning
confidence: 77%
See 1 more Smart Citation
“…ATR‐MIR spectroscopy disclosed the formation of unknown intermediates in the reaction. NMR and labelling ( 2 H and 18 O) experiments supported the DFT‐IR predicted reaction pathway such as cleavage of triple bond, amination and amidation to afford desired amide [75] …”
Section: Coupling Reactionsmentioning
confidence: 77%
“…NMR and labelling ( 2 H and 18 O) experiments supported the DFT-IR predicted reaction pathway such as cleavage of triple bond, amination and amidation to afford desired amide. [75] In 2017, Mehra et al reported an efficient methodology for regioselective synthesis of N-arylquinolones by using easily available DAIS and quinolones in aqueous medium under metal and ligand-free conditions. Electron donating group (EDG) as well as electron withdrawing group (EWG) substituted DAIS resulted in the formation of the desired products in good to excellent yields (42-91%).…”
Section: Cà N Couplingmentioning
confidence: 99%
“…The reaction between 2‐(phenylethynyl)benzoic acid and benzyl amine using Bu 4 N+ OAc‐ as a catalytic system in an aqueous medium, under microwave irradiation gave regioselectivelly 3‐hydroxyisoindolinones 164 (Table 6, entry 6) [237] . Benzylisoindoline‐1,3‐diones 165 can be prepared in good yields by the reaction of ortho ‐alkynylbenzaldehydes with primary amines in the presence of hypervalent iodine and sodium bicarbonate (Table 6, entry 7) [238] . When the terminal position of alkyne moiety of the ortho ‐alkynylbenzaldehydes are functionalized with ketones, isoindolinones 166 were obtained in yields ranging from 43 to 95% (Table 6, entry 8) [239] .…”
Section: Synthesis Of Isoindolinesmentioning
confidence: 99%
“…[237] Benzylisoindoline-1,3-diones 165 can be prepared in good yields by the reaction of ortho-alkynylbenzaldehydes with primary amines in the presence of hypervalent iodine and sodium bicarbonate (Table 6, entry 7). [238] When the terminal position of alkyne moiety of the ortho-alkynylbenzaldehydes are functionalized with ketones, isoindolinones 166 were obtained in yields ranging from 43 to 95% (Table 6, entry 8). [239] Hydroxylamine in THF at room temperature was utilized to promote the cyclization of ortho-alkynylbenzaldehydes leading to the synthesis of N-hydroxy-isoindolinones 167 (Table 6, entry 9).…”
Section: Transition Metal-free Synthesis Of Isoindolinesmentioning
confidence: 99%
“…Synthetic organic chemists are involved in a continuous effort to reveal the excellent Lewis acidic oxidizing characteristics of these reagents from the last decade of the 20 th century to recent years. These reagents led to rapid development in the modern field of C–C/C–X (X = O, N, halogens) coupling and cyclization reactions . Some chiral hypervalent iodine reagents were also in the limelight for asymmetric synthesis .…”
Section: Introductionmentioning
confidence: 99%